The effect of vitamin E and A supplementation on some hematological parameters and lactate levels of elite taekwondo players - Gorucu, A. (Turkish Journal of Sport and Exercise, 2017)
In this research it was aimed to investigate the effect of vitamin E and A supplementation on some hematological parameters of exercising taekwondo players. 21 healthy male elite taekwondo players were used as subjects. Subjects were separated into three groups. 300 mg/d vitamin E was given to vitamin E group, 100 mg/d vitamin A was given to vitamin A group and no vitamin supplementation was given to control group for 6 weeks. Taekwondo exercise was applied to all groups for 5 days per week during 6 weeks. Fatigue protocol was applied to subjects two times as pre-supplementation and post- supplementation. Blood samples from all groups were taken four times the 1st and 6th week before and after the exercise. Some hematological (RBC (red blood cell), WBC (white blood cell), PLT (platelet), HGB (hemoglobin), LYM (lymphocyte), HCT (hematocrit), MCV (mean corpuscular volume), MCH (mean corpuscular hemoglobin), MCHC (mean corpuscular hemoglobin concentration), RDW (red cell distribution width), MPV (mean platelet volume), PCT (procalcitonin), PDW (platelet distribution width ) parameters and lactate levels determined from taken blood samples were measured. It was determined significant level (p<0.05) increase in HGB, HCT, RDW, PDW, MCV, MCH, MPV, PCT and lactic acid amounts in samples taken after exercises, after and before supplementation. It was determined a decrease in HGB, HCT, PLT, MPV, RDW values in the vitamin E and A groups according to the control.